The ghost war [compact disc, unabridged] - Berenson, Alex (Berenson, Alex. John Wells novel., 2008)
Returning to Washington after a harrowing case in the Middle East, CIA agent and al-Qaeda infiltrator John Wells is selected to investigate a surge in Taliban activity with possible Asian ties.